Maize (Zea mays) bran as a biorefinery feedstock for the co-extraction of nutraceuticals and functional food compounds - Nkhoma, Mcphancio (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.